El relato del mensajero en Eurípides: concepto y estructura (Minerva, 2019)
This paper attempts to be a study of the messanger-speech concept and structure in Euripides' plays. The messanger's function, concept and attributes are also studied. The author focusses his attention on the messanger-speech sections and the differences among them. The messanger-speech is seen as the highest stage of tragic dramatism.